THE EFFECT OF SELF-EFFICACY FINANCIAL MEDIATION ON FACTORS AFFECTING FINANCIAL INCLUSION IN SMALL BUSINESSES IN WEST JAKARTA - Leon, Farah Margaretha (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
his study aims to examine and analyze the effect of financial self-efficacy mediation on the factors that influence financial inclusion in small businesses in West Jakarta. The dependent variables used in this study are commercial attitude and financial literacy, financial inclusion as an independent variable, and financial self-efficacy as a mediating variable. The sample of this study used 176 respondents who used a purposive sampling method. The data analysis model used is structural equation modeling (SEM). The results of this study indicate that financial attitude has a positive influence on financial inclusion. Financial literacy does not have a positive impact on financial inclusion. Financial position has a positive effect on financial inclusion that is mediated by financial self-efficacy. Financial self-efficacy does not mediate the impact of financial literacy on financial inclusion. This means that attitudes and self-confidence of commercial consumers increase access to formal financial services. This research implies that financial managers and the government need to create a sense of security and comfort for small business activists who want to use formal financial institutions, and the government also needs to make regulations and policies that support increased productivity in the use of financial services legal.Â Keywords: financial self-efficacy, financial inclusion, financial knowledge, financial attitudes